Overexpression of a Defensin-Like Gene CAL2 Enhances Cadmium Accumulation in Plants - Luo, Jin-Song; Xiao, Yan; Yao, Junyue; Wu, Zhimin; Yang, Yong; Ismail, Abdelbagi M.; Zhang, Zhenhua (Frontiers in Plant Science, 2020)
Accumulation and detoxification of cadmium in rice shoots are of great importance for adaptation to growth on polluted land and for limiting the transport of Cd to grains. However, the molecular mechanisms behind this phenomenon remain largely unknown. Defensin proteins play important roles in metal tolerance and accumulation in plants. In rice, the cell wall-localized defensin protein (CAL1) is involved in Cd efflux and allocation to the shoots. In the present study, we functionally characterized the CAL2 defensin protein and determined its contribution to Cd accumulation. CAL2 shared 66% similarity with CAL1, and its mRNA accumulation was mainly observed in roots and was unaffected by Cd stress, but its transcription level was lower than that of CAL1 based on the relative expression of CAL2/Actin1 obtained in this study and that reported previously. A promoter-GUS assay revealed that CAL2 was expressed in the root tips. Stable expression of the CAL2-mRFP fusion protein indicated that CAL2 was also localized in the cell walls. An in vitro Cd binding experiment revealed that CAL2 has Cd chelation activity. Overexpression of CAL2 increased Cd accumulation in Arabidopsis and rice shoots, but it had no effect on the accumulation of other essential elements. Heterologous expression of CAL2 enhanced Cd sensitivity in Arabidopsis, whereas overexpression of CAL2 had no effect on Cd tolerance in rice. These findings indicate that CAL2 positively regulates Cd accumulation in ectopic overexpression lines of Arabidopsis and rice. We have identified a new gene regulating Cd accumulation in rice grain, which would provide a new genetic resource for molecular breeding.